Clinicopathological features and prognostic factors for survival in patients with primary appendiceal adenocarcinoma - T. Udaka; T. Nishiyama; N. Watanabe; I. Endou; O. Yoshida; H. Asano; Y. Oshima; M. Kubo (World Cancer Research Journal, 2023)
Objective: Primary appendiceal adenocarcinoma accounts for 1% of colorectal tumors and is a rare malignancy. Peritoneal dissemination commonly occurs as part of the natural course of disease, following the sequence of luminal wall invasion, obstruction, and perforation.